Qualitative screening for redox‐sensitive elements in groundwater using the presence or absence of rust on irrigation center pivots - Jeffrey P. Westrop (Agrosystems, Geosciences & Environment)
Abstract Groundwater contaminants that can negatively impact human health, such as nitrate, uranium, arsenic, and manganese, are common in agricultural areas. The mobility and distribution of these contaminants in groundwater are strongly impacted by oxidation‐reduction (redox) processes. Groundwater redox, however, is difficult to determine without conducting time‐sensitive geochemical analyses. Prior research demonstrated that areas of low groundwater nitrate concentrations could be identified by the presence of rust on irrigation center pivots. This “rust” is a coating of iron (Fe) oxides formed by the incidental spraying of Fe‐rich groundwater on the surface of pivot. Thus, the pivot rust could be a qualitative indicator of reducing conditions where Fe is soluble in groundwater. Nitrate, arsenic, uranium, iron, and manganese from the irrigation wells associated with 29 pivots (16 rusted and 13 non‐rusted) in central Nebraska. Results indicate significantly higher concentrations of iron and manganese and significantly lower concentrations of nitrate and uranium in areas with rusted pivots, strongly suggesting a link between pivot rust and redox‐sensitive contaminants. Most of the rusted pivots in the study area are along the eastern edge of the subcrop of the Miocene Ogallala Group, where the alluvium overlies the Pierre shale, which could be the source of Fe and other metals in groundwater. These results underscore the utility of pivot rust as a rapid, non‐invasive indicator for redox‐sensitive elements in groundwater.